Pengaruh Motivasi Kerja Terhadap Kinerja Karyawan Dengan Kepuasan Kerja Sebagai Variabel Moderasi - Abdul Majid; Adi Lukman Hakim; Elvina Assadam (JAS-PT (Jurnal Analisis Sistem Pendidikan Tinggi Indonesia), 2021)
This study aims to describe work motivation, job satisfaction and employee performance and to analyze job satisfaction in moderating the effect of work motivation on employee performance. This research method with qualitative and quantative approaches. The population of this study were all employees of Hotel Pardise Batu, so that the sampling used total sampling technique. Descriptive data and moderated regression were used as data analysis. The results show that work motivation has an effect on employee performance, job motivation, job satisfaction and the interaction between work motivation and job satisfaction has a positive and significant effect on employee performance, and job satisfaction moderates the effect of work motivation and employee performance